HOW CAN EDUCATION SYSTEM OF SINGAPORE CONTRIBUTE TO NATION BUILDING (Jurnal Bahasa Lingua Scientia, 2010)
A nation’s character can be built through the education. In addition, the advancement of a nation can also be driven by the quality education. A good education will guarantee a nation’s wealth and its competitiveness in science and technology. A few decades ago, Indonesia was well known for its quality education system and the human resources. As the result, many Indonesian teachers were sent abroad to teach other nations. Yet, today from the Human Development Index, Indonesian must admit other nations’ superiority in their quality human resources. This article tries to portrait the education system of Singapore and its implication to its nation building.
Keywords: Education system of Singapore; nation building